Studi Komparatif Hasil Belajar Siswa Kelas Tahfidz dan Kelas Reguler Pada Mata Pelajaran Ekonomi Kelas 11 MA AL Asror Semarang - Hanifah, Nur Elliyana; Satyarini, Marhaeni Dwi; Setyaningsih, Sri (Universitas Ivet, 2025)
Madrasah Aliyah Al Asror organizes learning for regular class programs and tahfidz classes. Tahfidz class students are required to stay at the Islamic boarding school and participate in all activities at the Islamic boarding school, while regular class students are allowed to participate in learning at the Islamic boarding school but are not required to live at the Islamic boarding school. This research was conducted at MA Al Asror Semarang, aimed to find out (1) The learning outcomes of economic subjects of class 11 IPS 1 students of tahfidz class; (2) The learning outcomes of economic subjects of class 11 IPS 2 students of regular class; (3) Whether or not there is a difference in learning outcomes of economic subjects between class 11 IPS 1 students of tahfidz class and class 11 IPS 2 students of regular class. This study uses a quantitative approach with a comparative method. The population of the study was 46 students of grade 11 IPS, consisting of 17 students of the tahfidz class and 29 students of the regular class. Data collection techniques using documentation and interview methods. Data analysis using the Independent Sample T-Test technique for hypothesis testing. The results of the study showed: 1) The average learning outcomes of students in the tahfidz class were 85.74, in the high category. 2) The average learning outcomes of students in the regular class were 85.38, included in the high criteria; (3) The results of the Independent Sample T-Test obtained a coefficient of t = 0.393, a significant value (2-Tailed) of 0.697 > 0.05, so Ha was rejected, Ho was accepted, meaning: there was no difference in learning outcomes of students in the tahfidz class and students in the regular class.